2023
DOI: 10.3390/buildings13071609
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on the Behavior of Floating Geogrid-Encased Stone Column Improved Foundation

Abstract: The ordinary (OSC) and geosynthetic-encased stone column (ESC) with different bearing strata significantly influenced its behavior. The paper established seven models for studying the behavior of floating stone columns using the finite difference method (FDM). The effect of geogrid and column length on the load-settlement behavior, bulging deformation, failure mode, and load transfer coefficient were also analyzed based on proposal models. The results showed that the bearing capacity of F-OSCs and F-ESCs incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Researchers have conducted extensive theoretical and experimental work in this field and have found that the use of geosynthetics effectively improves bearing capacity and deformation [24][25][26]. Cheng et al [27] conducted a numerical simulation of a floating geogrid-encased stone column to analyze the failure mode and load transfer law of such composite foundations and found that the long column was more prone to generate bulging deformation. Ou Yang et al [28] investigated the effects of geosynthetic-encased and ordinary stone columns on acceleration amplitude and frequency based on model tests.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have conducted extensive theoretical and experimental work in this field and have found that the use of geosynthetics effectively improves bearing capacity and deformation [24][25][26]. Cheng et al [27] conducted a numerical simulation of a floating geogrid-encased stone column to analyze the failure mode and load transfer law of such composite foundations and found that the long column was more prone to generate bulging deformation. Ou Yang et al [28] investigated the effects of geosynthetic-encased and ordinary stone columns on acceleration amplitude and frequency based on model tests.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of facilitating PVD-assisted ground treatment, model testing, in situ monitoring, and numerical simulation are frequently used in evaluation by research and industrial communities [12,13]. Bo (2016) [10] demonstrated that current model-testing techniques for evaluating the optimal performance of PVD were limited.…”
Section: Introductionmentioning
confidence: 99%